2007
DOI: 10.1111/j.1399-6576.2007.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined photoplethysmographic monitoring of respiration rate and pulse: a comparison between different measurement sites in spontaneously breathing subjects

Abstract: Combined PPG respiration and pulse monitoring is possible, but there are significant differences between the respiratory and cardiac components of the PPG signal at different sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 28 publications
8
68
5
2
Order By: Relevance
“…This analysis confirms that the PO signal reflects both cardiac and respiration components of blood oxygenation modulation (see also Nilsson et al, 2007). Using spectral filtering, it was possible to isolate these components, which appeared to be shifted from the time of the mechanical events that cause them.…”
Section: Comparison Of Physiological Signalssupporting
confidence: 71%
See 2 more Smart Citations
“…This analysis confirms that the PO signal reflects both cardiac and respiration components of blood oxygenation modulation (see also Nilsson et al, 2007). Using spectral filtering, it was possible to isolate these components, which appeared to be shifted from the time of the mechanical events that cause them.…”
Section: Comparison Of Physiological Signalssupporting
confidence: 71%
“…When aligned to the R component of the The cardiac signal from the ECG (dark gray) covers a broad range of frequencies ranging from 0.5 to 3.5 Hz. The pulse oximetry (PO) signal (black) also has a peak corresponding to 15 events per minute, as well as a peak at approximately 60 events per minute (see also Nilsson et al, 2007). A minor high frequency peak can be found at about 2.25 Hz as well.…”
Section: Comparison Of Physiological Signalsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously, several investigators reported accurate estimation of vitals using PPG signal collected from the finger in comparison with ECG in healthy [58][59][60] and disease settings [61][62][63]. Investigations by Maeda et al [55] showed relatively high signal strength can be obtained over from the wrist but lacked signal to noise ratio assessments which is essential to estimating accurate biometrics.…”
Section: Figurementioning
confidence: 99%
“…Light-transmission configuration can be used in the finger but not in the forehead, where lightreflection is the only possible configuration. This affects to the PPG morphology, obtaining a smoother waveform when the signal is recorded in the forehead [6]. These characteristics in combination with the differences in arterial routes can generate differences in the estimated respiratory rate depending on the sensor location.…”
Section: Introductionmentioning
confidence: 99%